1993
DOI: 10.1111/j.1440-1827.1993.tb02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Segmental glomerular necrosis as an active index of IgA nephropathy: A study with 100 serial sections of 128 cases

Abstract: One hundred serial sections from each of 128 cases with immunoglobulin A (IgA) nephropathy were examined by light microscopy to clarify the relationship between segmental glomerular necrosis (SGN) and progression of glornerular injury. The cases were divided into five groups according to the percentage of glomeruli with cellular/fibrocellular (C/F) crescents, fibrous adhesion and/or sclerosis: grade I, 0%; grade It, ~2 0 % ; grade 111, 20-50%; grade IV, 5040%; and grade V, 80% or more. The serial sections reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The clinical and pathological characteristics of patients with IgAN are diverse and vascular lesions are commonly found in renal biopsies. For example, it was reported that segmental necrotizing lesions of glomerular capillaries, similar to those of Henoch–Schonlein purpura and antineutrophil cytoplasmic antibody (ANCA)‐positive systemic vasculitis, could be found in 10–30% of patients with idiopathic IgAN 15,16 . An earlier study by Feiner et al.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and pathological characteristics of patients with IgAN are diverse and vascular lesions are commonly found in renal biopsies. For example, it was reported that segmental necrotizing lesions of glomerular capillaries, similar to those of Henoch–Schonlein purpura and antineutrophil cytoplasmic antibody (ANCA)‐positive systemic vasculitis, could be found in 10–30% of patients with idiopathic IgAN 15,16 . An earlier study by Feiner et al.…”
Section: Discussionmentioning
confidence: 99%
“…This study showeda more favorable response to PSLtherapy in cases with than in those without C/F crescents and/or SGN during the course of PSLtherapy. In our previous study using 100 serial sections of 128 cases with IgA nephropathy, SGNas well as C/F crescents occurred more frequently than suggested previously and we suggested that repeated occurrence of the lesions mayparticipate in slowly progressive deterioration of renal function (15). In this regard, IgA nephropathy may be considered slowly progressive crescentic glomerulonephritis.…”
Section: Discussionmentioning
confidence: 88%
“…SGN can be found in IgAN. Shouno et al [15] reported that the inci- [19] reported that the incidence of the segmental necrotizing lesion was 10.3%. In our center, we found that the incidence of segmental necrotizing lesion was 6.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological features have been proved as risk factors for progression of IgAN and were important factors for guiding treatment [5,6,21,22] . Most of the research found SGN accompanied by crescents were indicative of the beneficial effects of corticosteroid therapy [13][14][15] . In D'Amico's research, about IgAN with SGN, the effect of corticosteroid was not defined [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation